Comparison of spectrolyser device measurements with standard analysis of wastewater samples in Novi Sad, Serbia - Mihajlović, I; Pap, S; Sremački, M; Brborić, M; Babunski, Darko; Dogo, M (Springer Science and Business Media LLC, 2014)
On-line monitoring was performed using spectrolyser equipment, coupled with laboratory analysis for samples collected from wastewater discharge in the city of Novi Sad, Serbia, during first 24 h of three and 48 h of six monitoring campaigns from December of 2012 to April of 2013. Significant correlation with R(2) > 0.9 was observed between laboratory analysis and spectrolyser measurements for chemical oxygen demand (COD) and biological oxygen demand (BOD) concentrations. COD/BOD5 ratio in combined industrial and municipal wastewater ranged from 1.2 to 2.0 indicating the presence of biodegradable organic matter which could be easily removed using aeration treatment process. Micro/trace element and/or heavy metals in wastewater samples were within the limits as per the standard prescribed for wastewater, and should not pose any serious hazard risk. However BOD, COD, ammonia and total phosphorus concentrations were measured above the limit value according to Serbian and EU legislation and should be reduced before discharging wastewater directly into the Danube River.